STUDENTS’ PERCEPTION ON THE USE OF ENGLISH SONGS IN THE ENGLISH LEARNING PROCESS - Nauval Chaidir (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: English learning process is a process which is done by both learners and educators. English learning process means there will be a teacher or a lecturer who will help their students in mastering English as their active language. But on the other hand, teaching English to students sometimes may be felt so hard for some educators. Many techniques and media are offered to ease and help them in teaching English, such as using English songs. The research was about the exploration of English students’ perception on the use of English songs in the English learning process. This study was conducted at University of Islam Malang with five chosen English Department students. Those five participants were coming from seventh semester. The data was analyzed qualitatively with interview which was conducted in only one time. The interview consisted of fifteen questions. It needed a week for the researcher to take data. To make the data more valid, the researcher did triangulation. The result of the research showed that the use of English songs could give many good effects that must be very useful for the participants. The use of English songs had positivity in increasing students’ English skills, such as Grammar, speaking skill, and listening skill. Also, English songs could enrich students’ English vocabulary. Nevertheless, there was an opinion found from the interview which said that sometimes the use of English songs in the English learning process was felt unenjoyable. The things that made it felt unenjoyable was that English songs were hard to understand for they often show the students’ many new and strange words. From this research, there are things which must be improved by the future researchers. It is suggested for them to more explore the students’ perception about the use of English songs. Also, in order to find more detail and satisfying result, it is suggested for the future researchers to find the perception based on English lecturer’s point of view.Key words: English learning process, English Song, English students